Measuring household uncertainty in EU countries - Gene Ambrocio (Bank of Finland, 2019)
I provide a measure of household uncertainty available for European Union (EU) countries. The measure draws from the same consumer survey data used to construct widely-used consumer sentiment indices. I find that increases in household uncertainty are followed by declines in consumer sentiment and household financial conditions. Using Euro Area-wide indices, I also find that the effects of increases in household uncertainty differ from increases in uncertainty from other sources such as financial markets and economic policy. Notably, household uncertainty shocks are inflationary. These results challenge the notion that (household) uncertainty shocks act like negative demand shocks.
URN:NBN:fi:bof-201909061440
Keywords: C32; D84; E37; 330